(untitled) (Historia, 2021)
The phenomenon of the "poor white" social class dominated much of the academic, media and entertainment spheres for the first half of the twentieth century. This article examines poor white women as depicted in both fiction and non-fiction in South African literature and demonstrates that there is a certain overlap in their depiction. By combining the two types of literature it shows that selected novels, specifically those written during the first half of the twentieth century by authors from the Realist genre, may be considered cultural historical sources in their own right - in terms of portraying the daily lives and struggles of poor white women trying to fit into a male-constructed ideology. As a rather marginalised sector, poor-white women, are examined in terms of the volksmoeder concept and attention is given to how the novels redefined this term.